The Spirit of Rasulullah Entrepreneurship Education For Elementary School at Sekolah Alam Bogor - Bastoni, Hepi Andi; Saefuddin, Didin; Husaini, Adian; Tamam, Abas Mansur (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
One of the important subjects that are taught at Sekolah Alam Bogor Elementary School is entrepreneurship. This subject is given to students from 1st grade to 6th grade. This particular lesson is considered important to build a sense of independence from an early age. The theory and practice of this lesson are taught to the students. Although generally, the curriculum requires more practice than theory. The researcher tried to record and capture the activities during the learning process on the entrepreneurship subject at Sekolah Alam Bogor Elementary School, to observe, to interview the involved parties, and to collect data, either directly from the source or indirectly. Then, the collected data was analyzed with a literature review referring to Rasulullahâ€™s life, especially when he was actively involved in the business world before his prophetic era began. Evidently by referring to the trustworthy old books and the analysis of the latest scholars. Based on the research, it is concluded that the curriculum of entrepreneurship applied at Sekolah Alam Bogor Elementary School is very effective to cultivate an entrepreneurial spirit in the students. Also, the spirit that is cultivated is very much in line with the entrepreneurship spirit of Rasulullah. Even though it still needs some additions and improvements.Â